To collaborate or not? the role of relationship-specific investments in small and medium-sized enterprises - Sukresna, Made; Mahfudz,; Hamilton, John Robert (Penerbit Universiti Kebangsaan Malaysia, 2024)
Past studies examined the benefits and drawbacks of relationship-specific investments (RSIs), but few compared the two simultaneously in the context of small and medium-sized enterprises (SMEs). This study aims to fill the gap in the literature by investigating the impact of different factors on manufacturer–retailer relationships in Indonesian SMEs. We argue that RSIs, collaboration, and opportunism can influence relationship performance, and RSIs can drive collaboration and opportunism. This research employs data from 200 small and medium-sized furniture manufacturers in Indonesia and tests the hypotheses using structural equation modeling. Findings show that the benefits of RSIs outweigh their drawbacks, and RSIs can directly enhance relationship performance, foster collaboration, and reduce the negative opportunistic tendencies of retailers in marketing channels. The findings also show that optimal RSIs and collaboration can reduce the detrimental impact of the opportunism of retail partners. This study suggests that SMEs prioritize and apply knowledge-based RSIs by intensively teaching their channel partners specific sales and furniture product maintenance techniques to promote further interactions with retailers, which may result in enterprise growth. In addition, SMEs should complement collaboration with a formal contract, because overdependence on an informal contract may result in a false sense of security over opportunism actions.